2010
DOI: 10.1577/1548-8446-35.4.175
|View full text |Cite
|
Sign up to set email alerts
|

Fish Habitat Degradation in U.S. Reservoirs

Abstract: As the median age of the thousands of large reservoirs (> 200 ha) in the United States tops 50, many are showing various signs of fish habitat degradation. Our goal was to identify major factors degrading fish habitat in reservoirs across the country, and to explore regional degradation patterns. An online survey including 14 metrics was scored on a 0 (no degradation) to 5 (high degradation) point scale by 221 fisheries scientists (92% response rate) to describe degradation in 482 reservoirs randomly distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 10 publications
1
32
0
Order By: Relevance
“…Snag cover is recognized as a particularly important element of littoral habitat complexity (Christensen et al 1996, Francis and Schindler 2006, Miranda et al 2010); therefore, we included snags as a separate…”
Section: Littoral Cover Complexity Index (Litcvrq)mentioning
confidence: 99%
“…Snag cover is recognized as a particularly important element of littoral habitat complexity (Christensen et al 1996, Francis and Schindler 2006, Miranda et al 2010); therefore, we included snags as a separate…”
Section: Littoral Cover Complexity Index (Litcvrq)mentioning
confidence: 99%
“…However, some studies have evaluated the role of fallen trunks and the impact of their removal on the biota of a given area and have also highlighted the role of submerged trunks in creating structure within habitats (Sass et al, 2006;Roth et al, 2007, Helmus & Sass, 2008Ahrenstorff et al, 2009). An extensive study by Miranda et al (2010), conducted in almost 500 North American reservoirs, revealed that the scarcity or the absence of macrophytes and submerged trunks is the main factor to be considered for the restoration of fish habitat in these environments.…”
Section: Introductionmentioning
confidence: 99%
“…Declines in fish diet, growth rate, biomass, and abundance correlate with reduced littoral physical habitat complexity (Bettoli et al 1993;Sass et al 2006). Anthropogenic regulation of water level regimes is a primary threat to fish species that use the littoral zone for all or part of their lives (Winfield 2004;Miranda et al 2010;Strayer and Findlay 2010). Annual winter drawdowns can reduce the availability and suitability of spawning habitat, limit the availability of winter habitat refuge from lethal DO concentrations (Cott et al 2008) and predation, decrease and alter food supplies, and alter the levels of predator-prey and competitive interactions via macrophyte structural and taxonomical composition alteration and density reduction (Wilcox and Meeker 1992).…”
Section: Fish Responsesmentioning
confidence: 99%